2019
DOI: 10.3389/fmars.2019.00713
|View full text |Cite
|
Sign up to set email alerts
|

Native Herbivores Improve Sexual Propagation of Threatened Staghorn Coral Acropora cervicornis

Abstract: Staghorn coral Acropora cervicornis was once spatially dominant on Caribbean reefs but is now threatened throughout its range. In recent years, advancements in ex situ sexual propagation of Caribbean corals have increased the viability of this management strategy. Thus, improving culture methods for sexually propagated corals is important to bolster the overall coral restoration portfolio and increase genetic diversity in restored populations. In both natural systems and culture scenarios, algae proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In order to prevent complete overgrowth of the juvenile corals, algae was manually removed from plugs and plug racks, and tanks were cleaned on a weekly basis. Importantly, this maintenance was solely to prevent corals from being smothered by mat-forming macroalgae and was not an attempt to represent any form of herbivory, a factor which can be influential when raising corals in an ex situ environment (Craggs et al 2019, Henry et al 2019. Despite these efforts, this algal bloom interfered with data collection and no data was recorded in September due to extensive algae cover.…”
Section: Coral Husbandrymentioning
confidence: 99%
“…In order to prevent complete overgrowth of the juvenile corals, algae was manually removed from plugs and plug racks, and tanks were cleaned on a weekly basis. Importantly, this maintenance was solely to prevent corals from being smothered by mat-forming macroalgae and was not an attempt to represent any form of herbivory, a factor which can be influential when raising corals in an ex situ environment (Craggs et al 2019, Henry et al 2019. Despite these efforts, this algal bloom interfered with data collection and no data was recorded in September due to extensive algae cover.…”
Section: Coral Husbandrymentioning
confidence: 99%
“…Coral larvae are easily transported across large distances in high numbers (Petersen et al, 2005), meaning that larvae produced under fully controlled conditions anywhere in the world can be used for direct re-seeding activities (Heyward et al, 2002;dela Cruz and Harrison, 2020). Alternatively, sexually propagated coral recruits and juvenile colonies can be reared in human care for periods of time ranging from a few weeks (Guest et al, 2014;Chamberland et al, 2015), to months (Henry et al, 2019), to a year or more (Craggs et al, 2020).…”
Section: Restoration Implicationsmentioning
confidence: 99%
“…Further, Craggs et al (2020) recently reported the first completed life cycle (i.e., production of an F2 generation) for a broadcast spawning coral in a fully controlled system. Beyond spawning, recent advances in rearing techniques for early post-settlement coral recruits have improved sexually propagated coral survival and growth in land-based systems (Craggs et al, 2019;Henry et al, 2019). Altogether, these advances have made sexual coral propagation in land-based systems a viable strategy for augmenting the genetic diversity that is currently available to restoration programs.…”
Section: Introductionmentioning
confidence: 99%
“…Coral reefs are one of the world's most diverse and fragile ecosystems. They are currently in global decline due to climate change, disease, and other stressors (Hoegh‐Guldberg et al, 2007; Hughes et al, 2003; Walton et al, 2018). The Caribbean region has been especially impacted by coral loss (Gardner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As the general practice of active coral restoration expands, land-based nurseries are receiving increased attention. Such nurseries are archiving living genetic diversity being lost in the wild and contributing to successes in sexual coral propagation (Chamberland et al, 2016;Craggs et al, 2017;Henry et al, 2019). Furthermore, many public aquariums maintain exhibits featuring live corals.…”
Section: Introductionmentioning
confidence: 99%